Management of social networks by universities category a in Ecuador [Gestión de redes sociales por parte de las universidades categoría a en Ecuador] - Puertas Hidalgo, R. (2016)
Universities in Ecuador face revolutionary change. The government has established sanctions and certain groupings in higher education. Fourteen universities were closed in 2012, and the rest were categorized A, B, C and D, with those in category A being the top universities and those in D being universities that do not meet all the requirements established by the Board of Evaluation, Accreditation and Quality Assurance in Higher Education (CEAACES). Within this framework, the research proposes to analyze the management of institutional social networks of category A, which includes Polytechnic National, EPN, Escuela Superior Politecnica del Litoral, ESPOL, and Universidad San Francisco de Quito, USFQ. Statistical analysis will review interaction and user engagement with the published content to demonstrate its reach and presence. USFQ is the university with greater presence and engagement on Facebook and Twitter and is making inroads into other networks frequently used by millennials.